Oral Microbiome: Streptococcus mutans/Caries Concordant-Discordant Children - Dinis, Márcia; Agnello, Melissa; Cen, Lujia; Shokeen, Bhumika; He, Xuesong; Shi, Wenyuan; Wong, David T. W.; Lux, Renate; Tran, Nini Chaichanasakul (Frontiers in Microbiology, 2022)
Dental caries remains the most common chronic disease in children, and the respective etiology is not fully understood. Though Streptococcus mutans is an important factor in the initiation and progression of caries, its presence is not always associated with the disease. The existence of caries discordant populations, in which S. mutans counts do not correlate with caries experience, poses a challenging problem. This study explored the possible correlation of S. mutans and other microorganism levels on caries-associated ecology of caries-concordant and discordant populations. A total of forty-seven children were analyzed in this study and stratified into four clinical groups based on their S. mutans levels in saliva (HS/LS: High/low S. mutans) and caries experience. Streptococcus mutans levels were determined by culture-based selective plating. The salivary microbiome of caries concordant and discordant populations was investigated by 16S rRNA gene sequencing and downstream bioinformatics analysis. The salivary microbial communities significantly clustered based on S. mutans levels and independent of their caries experience. In addition to S. mutans levels, significant differences in the abundance of other species were observed between HS and LS groups. Interestingly, disease-associated species such as Veillonella dispar, Streptococcus spp., and Prevotella spp. were significantly increased in HS groups and may contribute, in combination with S. mutans, to the caries progression. Furthermore, health-associated species exhibited higher abundance in the LS groups, such as Veillonella rogosae, Haemophilus sp., and Alloprevotella spp. but their possible contribution to the caries process remains to be elucidated. This study provides evidence that S. mutans may play a role in shaping the salivary microbial community. Our results highlight that future caries research should consider additional species as health/disease microbial markers in conjunction with S. mutans to improve diagnosis and caries management of the caries-discordant population.